The Atlantic Slave Trade / [electronic resource] - Klein, Herbert S. (Cambridge : Cambridge University Press, 2010)
This survey is a synthesis of the economic, social, cultural, and political history of the Atlantic slave trade, providing the general reader with a basic understanding of the current state of scholarly knowledge of forced African migration and compares this knowledge to popular beliefs. The Atlantic Slave Trade examines the four hundred years of Atlantic slave trade, covering the West and East African experiences, as well as all the American colonies and republics that obtained slaves from Africa. It outlines both the common features of this trade and the local differences that developed. It discusses the slave trade's economics, politics, demographic impact, and cultural implications in relationship to Africa as well as America. Finally, it places the slave trade in the context of world trade and examines the role it played in the growing relationship between Asia, Africa, Europe, and America. This new edition incorporates the latest findings of the last decade in slave trade studies carried out in Europe and America. It also includes new data on the slave trade voyages which have just recently been made available to the public.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).